A correlation between structural features of an amphiphilic diblock copolymer in solution and the structure of the porous surface in an integral asymmetric membrane. (22nd September 2017) - Dami, Sofia; Abetz, Clarissa; Fischer, Birgit; Radjabian, Maryam; Georgopanos, Prokopios; Abetz, Volker
Abstract: A correlation between the pore size of isoporous block copolymer membranes produced via the combination of self-assembly with non-solvent induced phase separation (SNIPS) on one side and the macromolecular dimensions of the block copolymer in the casting solution on the other side is presented. Dilute solutions of a polystyrene- b -poly(4-vinylpyridine) (PS- b -P4VP) diblock copolymer and corresponding polystyrene (PS) and poly(4-vinylpyridine) (P4VP) homopolymers similar to the respective blocks of the diblock copolymer are investigated separately by static and dynamic light scattering (SLS, DLS) in solvent mixtures of tetrahydrofuran/ N, N -dimethylformamide (THF/DMF). These measurements provide information about the size of the individual polymers in solution. Solutions of the diblock copolymer at higher concentrations are studied furthermore by small-angle X-ray scattering (SAXS) and cryo-scanning electron microscopy (cryo-SEM) in order to estimate the size of self-assembled structures in concentrated solution, as well as by scanning electron microscopy (SEM) in the final membrane. The pore radius of the selective layer in the resulting membrane obtained by SNIPS is shown to be similar to the hydrodynamic diameter of the pore forming block, as determined in dilute solution. Graphical abstract: Highlights: Investigation of structure formation from dilute solution to final membrane. Regular pore size via SNIPS by casting a solution very close to ordering. Membrane pore size relates to hydrodynamic radius of pore forming block.